Nerve conduction studies through landmark based recording and effects of hand length - Sai Deepak Yaranagula; Venkata Krishna Chaitanya Koduri; P. Suresh Babu; Thriveni Veligonda (Scientific Reports, 2023)
Abstract As per existing guidelines, the distance between stimulator and recording electrodes in nerve conduction studies (NCS) should be the same (fixed) in all the subjects, i.e., it should not be based on anatomical landmarks. However, there are no studies comparing fixed distance recordings with landmark based NCS. We postulated that hand length can influence the NCS parameters in fixed distance recordings and this can be nullified using landmark based recordings. To test this theory, we performed NCS in 48 normal subjects as per standard guidelines (standard protocol) and then compared it to NCS with ulnar styloid as the landmark (modified protocol). NCS were performed on median and ulnar nerves of the right upper limb. Three motor NCS parameters including distal latency, compound muscle action potential (CMAP) amplitudes and nerve conduction velocities were measured. Sensory nerve action potential (SNAP) amplitudes and conduction velocities were the two sensory parameters measured. On analysis, ulnar motor conduction velocity was the only parameter affected by hand length in both standard and modified protocols. Modified protocol did not have any additional advantage to the standard protocol advised by NDTF. We conclude that the NDTF guidelines are therefore reasonable when considering the effects of hand length. Possible reasons for this result including anatomical and anthropometric explanations are discussed.